The Theory of Limited and Unlimited Discrimination - Leontief, W. (Quarterly Journal of Economics, 1940)
I. Practice of discriminating monopolists often under conditions at variance with the common theoretical assumptions, 490. — II. The theoretical problem of unlimited and limited discrimination in its simplest form, 491. — III. Limiting conditions, 491. — IV. Fixed price difference, 492. — V. Varying price difference, 493. — VI. Adjusting the price difference to maximize profit, 495. — VII. Increase or decrease of prescribed price difference might increase profits, 496. — VIII. Comparison of discriminating monopoly and monopoly without discrimination, 496. — IX. The necessary restrictive assumptions, 497. — X. Illustration of proposition II, 499. — XI. Conclusion, 500.